Immunostimulative Activity of Low Molecular Weight Chitosans in RAW264.7 Macrophages - Wu, Ning (Mar Drugs, 2015)
Chitosan and its derivatives such as low molecular weight chitosans (LMWCs) have been reported to exert many biological activities, such as antioxidant and antitumor effects. However, complex and molecular weight dependent effects of chitosan remain controversial and the mechanisms that mediate these complex effects are still poorly defined. This study was carried out to investigate the immunostimulative effect of different molecular weight chitosan in RAW264.7 macrophages. Our data suggested that two LMWCs (molecular weight of 3 kDa and 50 kDa) both possessed immunostimulative activity, which was dependent on dose and, at the higher doses, also on the molecular weight. LMWCs could significantly enhance the the pinocytic activity, and induce the production of tumor necrosis factor α (TNF-α), interleukin 6 (IL-6), interferon-γ (IFN-γ), nitric oxide (NO) and inducible nitric oxide synthase (iNOS) in a molecular weight and concentration-dependent manner. LMWCs were further showed to promote the expression of the genes including iNOS, TNF-α. Taken together, our findings suggested that LMWCs elicited significantly immunomodulatory response through up-regulating mRNA expression of proinflammatory cytokines and activated RAW264.7 macrophage in a molecular weight- and concentration-dependent manner.